Exposure During Pancreatic Surgery. Do We Have to Examine the Falciform and Round Ligaments for Pancreatic Cancer Metastasis? - Ben-Ishay, Offir; Ariche, Arie; Lachter, Jesse; Kluger, Yoram (JOP. Journal of the Pancreas, 2011)
Context Metastatic and locally advanced disease is unfortunately a common clinical occurrence in patients affected by pancreatic cancer. The most frequent sites of metastasis are the liver and the peritoneal lining. The falciform and round ligaments are routinely resected and sent for pathology, but no metastases have ever been reported. Objective In this study, we assess whether the falciform and round ligaments are possible sites for metastases and if routine pathology examination of these structures is justified. Design Retrospective, single institution study. Patients The charts of all patients who underwent pancreatic resection from June 2005 through January 2011 were reviewed retrospectively. Data on age, gender, type of operation performed, preoperative CA 19-9 levels, vascular and perineural invasion, tumor differentiation and pathological staging were retrieved from the hospital electronic data base. Only patients with malignant lesions of the pancreas were included in the study. Main outcome measures Presence of pancreatic metastasis in the falciform and round ligaments. Results Fifty-seven patients were included in the study. Forty patients had undergone pancreaticoduodenectomies, 10 subtotal pancreatectomies, 2 total pancreatectomies, and 1 distal pancreatectomy. Four patients had exploratory laparotomy but exploration revealed stage III or IV disease, thus the planned resection was not carried out. The falciform and round ligaments were all negative for metastasis in all patients. Discussion Metastatic progression of pancreatic cancer is poorly understood. Theoretically, metastases to the falciform and round ligaments could occur by either contiguous, hematogenic or lymphatic spread. In our study, none of the patients had metastases to the falciform and round ligaments, regardless of the pathological staging. Conclusion We concluded that routine pathological examination of the falciform and round ligaments is not justified if the surgeon elects to remove the structures for ease of exploration and retraction during surgery. This may lighten the workload and reduce costs in a busy pathology laboratory. Image: Rambam Health Care Campus. Haifa, Israel.